PERLAKUAN STABILISASI, FERMENTASI, SERTA APLIKASI BEKATUL PADA PRODUK PANGAN MIE DAN ROTI: KAJIAN PUSTAKA - Meitiara Nanda Herisetianis; Hermawan Seftiono (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2023)
Bran is a side result of rice milling. Bran has a high content of free fatty acids, nutrients, and bioactive components. Bran stabilization method is a way to reduce the content of free fatty acids in bran. Nutrients and bioactive components in bran can be improved by the fermentation process. Nutrients in bran can also be developed as a functional food. The purpose of this study was to find out the influence of the best methods of stabilization treatment, the influence of fermentation treatment, as well as the influence of the addition of bran on noodle and bread products. The method in this study was to collect data based on FFA, PV, and TBA analysis on bran stabilization, proximal analysis, ferulat acid, Î³-oryzanol, and flavonoids in bran fermentation, proximal analysis, and antioxidant analysis in products. Bran stabilization treatment is carried out by three methods, namely Infrared, ohmic heating, and microwave. Microwave method is able to inhibit the content of FFA (2.04%) and TBA (0.42%) in bran, infrared method is able to inhibit PV value (2.90%). While the fermentation treatment of bran is done with various types of microbes such as gur, yeast, and lactic acid bacteria. Fermentation of bran with the gure R. oryzae can increase the levels of proximal, ferulatic acid in bran. Application of products on bran is done on noodle and bread products. Bran products with the addition of 45% bran in bread products are able to increase proximal levels (ash content 3.98%, fat content 7.18%, and protein levels 13.50%), while in the highest antioxidant analysis is in noodle products the addition of bran 10% by 66%.Bran is a side result of rice milling. Bran has a high content of free fatty acids, nutrients, and bioactivecomponents. Bran stabilization method is a way to reduce the content of free fatty acids in bran. Nutrients andbioactive components in bran can be improved by the fermentation process. Nutrients in bran can also bedeveloped as a functional food. The purpose of this study was to find out the influence of the best methods ofstabilization treatment, the influence of fermentation treatment, as well as the influence of the addition of branon noodle and bread products. The method in this study was to collect data based on FFA, PV, and TBA analysison bran stabilization, proximal analysis, ferulat acid, Î³-oryzanol, and flavonoids in bran fermentation, proximalanalysis, and antioxidant analysis in products. Bran stabilization treatment is carried out by three methods,namely Infrared, ohmic heating, and microwave. Microwave method is able to inhibit the content of FFA(2.04%) and TBA (0.42%) in bran, infrared method is able to inhibit PV value (2.90%). While the fermentationtreatment of bran is done with various types of microbes such as gur, yeast, and lactic acid bacteria.